Metaphorical Thinking CoRelEx Spatial Students on Trigonometry Word Problem Solving Ability - Kursius, Catherine Mentaya; Muttaqien, Anwar; Istadi, Istadi (Jurnal Riset Pendidikan Matematika, 2025)
Problems in the reality of our lives require mathematics to be solved often using analogies in their solutions or also called metaphors. The condition of these problems requires students to develop abilities that emphasize the development of relationships between mathematical concepts and real phenomena in the surrounding environment. The method used in this study is descriptive qualitative with purposive sampling. The study was conducted at a public senior high school in Central Kalimantan during the 2024–2025 academic year, with 3 spatial students as subjects with Visual, Auditory and Kinesthetic learning styles in class X room H. This study aims to determine the metaphorical thinking process of students when solving trigonometry word problems. By using metaphorical thinking skills, students' mathematical understanding process becomes more meaningful because they can see, form, and map mathematical concepts to real concepts according to experience.